(untitled) (Ustozlar uchun, 2025)
This article presents a comprehensive literary and philosophical analysis of Aleksandr Faynberg’s poem that reflects on time, aging, and moral self-assessment. The poem explores the paradox of physical aging accompanied by emotional and spiritual rejuvenation, raising profound questions about fate, guilt, and the ultimate meaning of human life. Through compact yet powerful imagery, Faynberg challenges conventional perceptions of time as a linear and irreversible force. The study examines the poem’s temporal paradoxes, ethical undertones, existential questioning, and poetic form, situating it within the broader context of Faynberg’s humanistic worldview. The analysis demonstrates how personal introspection is transformed into a universal meditation on responsibility, inner growth, and the uncertainty of one’s final destiny.